Bringing Math to Life: Provide Students Opportunities to Connect their Lives to Math - Carol D. Benson-O'Connor; Christina McDaniel; Jason Carr (Networks: An Online Journal for Teacher Research, 2019)
Math journals provide students with opportunities to articulate their understanding of math concepts and/or their frustrations with the gaps in those understandings. Their use supports metacognitive thinking to enhance understanding and application. This study took a look at the use of math journals by fourth grade students as a conduit for critical thinking, reflection, and real world math application. For this study, student journal entries consisted of identification of a real-life event, the use of a problem-solving strategy learned during class instruction, narrative of both the problem’s description as well as the rationale for choosing the problem, and the use of a numeric or pictorial model with solution. Students shared his/her journal entry with the entire class. Through this research, I witnessed evidence of growth in mathematical understanding, computing and a deeper connection to math’s many real-life applications in the lives of elementary students.
Keywords: Math; Math Journals; Journals; Authentic Learning; Metacognition; Writing